The Satisfaction And Performance Of Regional Civil Servants At The Service Of Youth And Sports In East Nusa Tenggara Province - Deford Nasareno Lakapu (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
This research was motivated by the impact of low job satisfaction, which was generated from low employee attendance and declining quality of performance. While this picture of Regional Civil Servants’ decline in performance can be seen from many of regional civil servants who left the office without a definite reason and worked only so long as it reduces the level of professional development as regional civil servants themselves, in addition, it also reflects the lack of responsibility and weak appreciation of its role as regional civil servants, particularly at the East Nusa Tenggara Provincial Youth and Sports Office. Thus, the formulation of the problem in this research is: 1) how does the perception of civil servants affect work motivation, hygiene, job satisfaction, and performance at the East Nusa Tenggara Provincial Youth and Sports Office?; 2) is the motivation factor and hygiene factor influencing the job satisfaction of civil servants at the East Nusa Tenggara Provincial Youth and Sports Office?; 3) are motivation and hygiene factors affecting the performance of civil servants at the East Nusa Tenggara Provincial Youth and Sports Office?: 4) does job satisfaction affect the performance of civil servants at the East Nusa Tenggara Provincial Youth and Sports Office? The population in this study are all civil servants in the East Nusa Tenggara Provincial Youth and Sports Office amounted to 126 people. Given the research subject is less than 200, then all of the population sampled. The type of data this study are primary and secondary data. Data analysis tools are SEM (Structural Equation Modeling), which is operated through a program AMOS 16.0 (Hair et al, 1998; Ferdinand, 2014). Results of the data analysis stated that the variable perceptions motivating factor (71.93%), hygiene factor (71.37%), job satisfaction (70.98%) and performance (72.35%) Civil Servants of the East Nusa Tenggara Provincial Youth and Sports Office, so each variable in both categories.Based on these findings, it is suggested that East Nusa Tenggara Provincial Youth and Sports Office to achieve job satisfaction and optimal performance of the indicators of qualitative, quantitative, efficiency and productivity, the local government of East Nusa Tenggara Province shall improve indicators of a variable factor of motivation and hygiene.